Справка (К вопросу об источниковедении и некоторых других вопросах) [A Background Check (On the Question of Archival Sources and Some Other Questions] - Ravdin, Boris (Slavica Revalensia, 2023)
This is a rejoinder to the speech from December 9, 2021, which served the purpose of providing Russia’s Supreme Court with a pretext for the closure of Memorial—a human rights organization founded in 1992 in Moscow, whose mission was to record crimes against humanity in the USSR and Russia and foster the rehabilitation of political prisoners.